Peranan Majelis Gereja Meningkatkan Pertumbuhan Rohani Pemuda Di GGRI Imanuel Dungkan Kecamatan Teriak - Waang, Sofia Kristin; Kapoh, Daniel Marciano; Somantik, Henni; Sipayung, Gerhard Eliasman (PT. Bangun Harapan Bangsa, 2024)
Some of the young people at GGRI Dungkan Congregation lack the motivation to participate in worship due to their inclination towards laziness, gaming, traveling in large groups, and a lack of suitable companions for worship. To address this issue, the church council needs to take an active role in fostering the spiritual growth of the youths at GGRI Imanuel Dungkan. The church council should develop teaching methods that resonate with the lives of today's youth, guiding them onto the right path. The purpose of this study is to investigate the church council's role in enhancing the spiritual development of young people. Qualitative research methods, including observation, interviews, and literature study, were used. The findings revealed that the youth's at GGRI Immanuel Dungkan Congregation desire the church council to impart accurate teachings using effective methods to enhance their spiritual growth. The more sincere the church council is in educating, teaching, and guiding the youth, the more proactive the youth will be in participating in worship.